Penambahan Vitamin C Pada Pengencer Fosfat Kuning Telur Semen Kalkun Yang Disimpan Pada Suhu 5°C (THE ADDITION OF VITAMIN C IN THE EGG YOLK PHOSPATE DILUENT OF TURKEY SEMEN STORED AT 5°C ) - Trilaksana, I Gusti Ngurah Bagus; Ndun, Rinna Noviyati; Bebas, Wayan (Buletin Veteriner Udayana; Vol. 7 No. 2 Agustus 2015, 2015)
The purposes of this research were to determine the motility and viability of turkey sperm on egg yolk phosphate diluent with the addition of various concentration of vitamin C stored at 5oC. The source semen from one and half years old turkey, semen diluted with eggyolk phosphate addition with vitamin C 0 mg/ml (without vitamin C), 0.1 mg/ml, 0.2 mg/ml and 0.3 mg/ml respectively. Observation was done every 12 hours for 72 hours. The results showed thataddition of vitamin C significantly difference on motility and viability of turkey stored at 5oC theaddition of 0.3 mg/ml vitamin C gives the best results in maintaining motility and viability of turkey sperm after 72 hours. In Conclusion, the addition of 0.3 mg/ml vitamin C in egg yolk phosphate diluent able to maintain motility (69.07%) and viability (71.64%) turkey sperm stored at 5oC.
Keywords: turkey’s semen, vitamin C, motility, viability